In-situ alloying of maraging steel with enhanced mechanical properties and corrosion resistance by laser directed energy deposition - Lek, Yung Zhen (2024)
Maraging steels are known for their exceptional strength derived from the martensite matrix and nano-precipitate strengthening. However, the trade-off to the high strength is often a loss of ductility and minimal strain hardening. Introducing metastable austenite to the matrix to activate transformation-induced plasticity (TRIP) is an effective approach to achieve high strength and ductility synergy. Existing methods to introduce TRIP into additively manufactured maraging steels are limited by the compositions of pre-alloyed powder or additional heat treatment steps. In-situ alloying via the laser directed energy deposition (L-DED) process allows flexibility in tailoring the alloying composition to achieve an austenite–martensite microstructure. Herein, we develop a TRIP–maraging steel by in-situ alloying of M789 with 316L (4–8 wt%) during the L-DED process. The addition of 316L facilitates austenite reversion in solution-treated maraging steel. As a result, the TRIP–maraging steel exhibits a 76 % increase in uniform elongation at the expense of a minimal sacrifice of strength. Furthermore, the corrosion resistance of the TRIP–maraging steel is enhanced. This work showcases a pathway to developing superior alloys by in-situ alloying via additive manufacturing.